2023
DOI: 10.3390/ma16113907
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of WC-Co Specimens with Internal Channels

Abstract: Most material removal in modern manufacturing is currently performed using tools with indexable inserts. Additive manufacturing allows for the creation of new, experimental insert shapes and, more importantly, internal structures, such as channels for coolant. This study deals with developing a process for efficiently manufacturing WC-Co specimens with internal coolant channels with a focus on obtaining a suitable microstructure and surface finish, especially inside the channels. The first part of this study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Internal cracks are common defects that appear in AM components, especially in WC-Co materials, usually due to the development of high thermal stresses during the process. Hence, their occurrence must be controlled [13,[28][29][30][31][32]. Some research demonstrated that these stresses are generated during solidification [33,34].…”
Section: Macrostructural Investigation Of the Sample In The As-built ...mentioning
confidence: 99%
“…Internal cracks are common defects that appear in AM components, especially in WC-Co materials, usually due to the development of high thermal stresses during the process. Hence, their occurrence must be controlled [13,[28][29][30][31][32]. Some research demonstrated that these stresses are generated during solidification [33,34].…”
Section: Macrostructural Investigation Of the Sample In The As-built ...mentioning
confidence: 99%
“…For the last ten years, there has been an increase in the research on AM with respect to tungsten carbide and cermets [4][5][6]. They have been tested with powder bed fusion (PBF) [7][8][9][10][11][12][13][14], binder jetting (BJT) [15][16][17], material extrusion (MEX) [18][19][20][21][22][23][24], and vat photopolymerization (VPP) [25]. Although they still underperform compared to the pressing and sintering method [26,27], they still possess advantages related to design freedom, which can justify the use of AM for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, heating and cooling rates are extremely fast [7,12], and particularly high energy outputs are needed to achieve sintering temperatures. In hardmetals and cermets, the high temperatures, which are reached in the center of the energy beam, are well above the melting temperature of cobalt; this entails evaporation during the consolidation process, which results in the embrittlement of the material [7,8,10,[12][13][14]. The heating/cooling thermal cycles are so fast that the thermal shock induced is enough to result in the development of cracks and delamination [9].…”
Section: Introductionmentioning
confidence: 99%